2011
DOI: 10.1889/1.3621354
|View full text |Cite
|
Sign up to set email alerts
|

34.3: Multi‐user 3D Film on Directional Sequential Backlight System

Abstract: Considering full resolution and without 3D glasses, timemultiplexed type is the better choice for 3D display, such as directional sequential backlight system. However, the current directional sequential backlight system can only produce a singleuser 3D display provided 3D image for single observer. Thus, the multi-user 3D film was proposed to add in front of the directional sequential backlight system and make the display become a multiuser (each observer watches the same image) 3D display provided full-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Autostereoscopic display based on directional backlight can deliver full-resolution images to each viewing zones sequentially, which significantly improves the 3D experience for observers. 3D prism film is widely used in the directional backlight-based autostereoscopic display [1][2][3]. Schultz et al [1] suggested a full-resolution autostereoscopic 3D display using a directional backlight with shallow prism structure, a 3D film with the top lenticular and bottom prismatic features, and an LCD panel.…”
Section: Introductionmentioning
confidence: 99%
“…Autostereoscopic display based on directional backlight can deliver full-resolution images to each viewing zones sequentially, which significantly improves the 3D experience for observers. 3D prism film is widely used in the directional backlight-based autostereoscopic display [1][2][3]. Schultz et al [1] suggested a full-resolution autostereoscopic 3D display using a directional backlight with shallow prism structure, a 3D film with the top lenticular and bottom prismatic features, and an LCD panel.…”
Section: Introductionmentioning
confidence: 99%
“…Basically they can display the stereoscopic image only to one viewer. Though there have been a few trials to increase the number of possible viewers [7], [8], the viewing position is still limited. One way to attain autostereoscopy with more viewpoints is to use a directional backlight composed of a large aperture convex lens and a dot-matrix backlight panel [10].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, they can display a stereoscopic image to a single viewer only. Though there have been a few trials to increase the number of possible viewers, 7,8 the viewing position is still limited.…”
Section: Introductionmentioning
confidence: 99%